2008
DOI: 10.1016/j.jacc.2007.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Intra-Abdominal Pressure in Acute Decompensated Heart Failure

Abstract: Elevated IAP is prevalent in patients with ADHF and is associated with impaired renal function. In the setting of intensive medical therapy for ADHF, changes in IAP were better correlated with changes in renal function than any hemodynamic variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
206
1
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(226 citation statements)
references
References 27 publications
2
206
1
17
Order By: Relevance
“…It has been know for several years that high central venous pressure (CVP) and even high intra-abdominal pressure from ascites may reduce GFR (40,41). Animal studies have consistently shown that increasing renal venous pressure by approximately 20-25 mmHg in the isolated dog or rat kidneys caused a profound decrease in renal perfusion accompanied by a sharp drop in the GFR, sodium excretion, and urine flow.…”
Section: Role Of High Venous Pressure In the Pathogenesis Of Crsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been know for several years that high central venous pressure (CVP) and even high intra-abdominal pressure from ascites may reduce GFR (40,41). Animal studies have consistently shown that increasing renal venous pressure by approximately 20-25 mmHg in the isolated dog or rat kidneys caused a profound decrease in renal perfusion accompanied by a sharp drop in the GFR, sodium excretion, and urine flow.…”
Section: Role Of High Venous Pressure In the Pathogenesis Of Crsmentioning
confidence: 99%
“…Hence, the exact mechanisms to explain the inverse relationship between high renal venous pressure and GFR in patients with HF are likely to be highly complex. Nevertheless, in patients with ascites or raised CVP, paracentesis or ultrafiltration has been shown to improve renal dysfunction (41). However, in the Cardiorenal Rescue Study in Acute Decompensated Heart Failure, ultrafiltration was not associated with improvement in renal function, although that study was not designed to address this particular question (45).…”
Section: Role Of High Venous Pressure In the Pathogenesis Of Crsmentioning
confidence: 99%
“…IAP is an independent risk factor for AKI development and may also explain the cardiorenal syndrome [40][41][42][43] . Dalfino et al [44] put IAP into relation with RIFLE criteria by showing intra-abdominal hypertension to be an independent predictive factor of acute renal failure, defined as failure class of RIFLE criteria [45,46] .…”
Section: Acute Respiratory Distress Syndromementioning
confidence: 99%
“…Among them, Damman et al (16) investigated the cardiorenal interactions in a retrospective manner across the entire spectrum of cardiovascular diseases with or without overt picture of heart failure, while Uthoff et al (9) explored the impact of the hemodynamic congestion on renal function in the setting of the acute decompensated heart failure requiring hospitalization. Besides, our search was influenced also by interesting insights ensued from some studies by Mullens et al (17,18) which would suggest that the presence of venous congestion may be the strongest hemodynamic determinant for the development of worsened renal function. Overall these studies would corroborate the concept that impact of systemic and renal venous congestion overcomes even that exerted by low cardiac output as regards the genesis and/or aggravation of renal dysfunction in CHF patients.…”
Section: Introductionmentioning
confidence: 99%